2019
DOI: 10.1242/bio.041327
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone abolishes cognition impairments as well as BDNF and neurotensin disturbances in a rat model of autism

Abstract: We have shown that exposure of rats to lipopolysaccharide (LPS) during gestation induces autistic-like behaviors in juvenile offspring and pioglitazone post treatment corrects social and communication deficits. The first objective of the present study was to evaluate the cognition of the rats, because this is also a behavioral sphere committed in autism. Second, biomarkers related to pioglitazone pathways and autism were studied to try to understand their mechanisms. We used our rat model of autism and pioglit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Kirsten et al established a mouse model for ASD by prenatal Lipopolysaccharide exposure and reported autistic like behavior and reduced NTS (protein) plasma levels in male offspring. Postnatal treatment with the anti-diabetic drug Pioglitazone corrected social and communication deficits and abolished the reduction in the NTS levels [80,81]. We found reduced Nts mRNA levels in VPA exposed male and female mice that were corrected by SAM administration.…”
Section: Discussionmentioning
confidence: 73%
“…Kirsten et al established a mouse model for ASD by prenatal Lipopolysaccharide exposure and reported autistic like behavior and reduced NTS (protein) plasma levels in male offspring. Postnatal treatment with the anti-diabetic drug Pioglitazone corrected social and communication deficits and abolished the reduction in the NTS levels [80,81]. We found reduced Nts mRNA levels in VPA exposed male and female mice that were corrected by SAM administration.…”
Section: Discussionmentioning
confidence: 73%
“…Our analysis of both young and older adult MIR offspring showed a persistent elevation in pro-inflammatory cytokines in the blood and increased brain-wide increases in microglia, suggesting a chronic inflammatory state across the life-span compared to age-matched controls. Both clinical and pre-clinical studies have previously reported some success in the clinical treatment of ASD in children with an anti-inflammatory drug, pioglitazone, which improved behavioral phenotypes along with reducing neuro-inflammation [216][217][218][219][220][221][222][223][224] . We also found a concomitant chronic elevation of mTOR signaling in the neurogenic adult subventricular niche 118 and now in several more regions in adult (cortex, amygdala, and striatum).…”
Section: Discussionmentioning
confidence: 99%